2014
DOI: 10.1002/lary.25107
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oxymetazoline on nasal flow and maximum aerobic exercise performance in patients with inferior turbinate hypertrophy

Abstract: 1b.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…found that the decongestant response was stronger for intranasal xylometazoline after 15 min than daily administration of intranasal mometasone furoate after 28 days. It is worth noting that only three studies included patients with AR, 1975–1977 the remainder consisted of healthy participants 1971–1974 …”
Section: Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…found that the decongestant response was stronger for intranasal xylometazoline after 15 min than daily administration of intranasal mometasone furoate after 28 days. It is worth noting that only three studies included patients with AR, 1975–1977 the remainder consisted of healthy participants 1971–1974 …”
Section: Managementmentioning
confidence: 99%
“…Onset of action is within 10 min, 1973 and duration of the effect lasts up to 12 h 1977 . There are also improvements in objective measures of nasal congestion/blockage, including nasal airway resistance, measures of nasal cavity volume for airflow, and PNIF 1972–1976 . Measures of nasal cavity volume for airflow exhibit a clear dose–response relationship across doses ranging from 6.25 to 50 μg, with nasal airway resistance requiring a higher threshold dose of 25 μg before significant changes in nasal patency are seen 1974 .…”
Section: Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxymetazoline, commonly marketed under the brand name Afrin, is a full α1 receptor agonist and a partial α2 receptor agonist. When oxymetazoline binds the alpha receptors found on the inferior turbinate vasculature, vasoconstriction occurs, the turbinate decongests, and nasal resistance decreases (Gómez-Hervás et al 2015). Oxymetazoline has been shown to be arguably the strongest decongestant, achieving the most rapid onset, longest duration of action, and greatest improvement in airway patency when compared with pseudoephedrine, the next strongest decongestant (Connell and Linzmayer 1987).…”
Section: Pharmacologymentioning
confidence: 99%
“…Despite these changes, the nasal airway contributes as little as 10 per cent of the overall minute ventilation at maximal exercise intensity 4 . The relative unimportance of the nasal airway can be demonstrated by the disappointing results of attempts to increase aerobic capacity by reducing nasal resistance through the use of ‘nasal dilator strips’ 5 – 7 or a pharmacological decongestant 8 . Equally, there is no hindrance to maximal aerobic performance when wearing an occlusive nose clip 9 .…”
Section: Normal Nasal Physiologymentioning
confidence: 99%